The Abbey complex in Middelburg an architectonic fraud? (Bulletin KNOB, 2003)
As regards scale and history the Abbey of Middelburg is one of the most important monuments in the Netherlands. The powerful Abbey, founded in the twelfth century, lost its religious function in the sixteenth century, after which the Court of the province of Zeeland found accommodation here.In the course of time the architectural situation of the complex deteriorated, also because it was used for an increasing variety of purposes.  Due to the efforts of Victor de Stuers the complex was restored around the turn of last century, an extensive and ambitious project, which was very important for the continued existence of the Abbey. The Middelburg architect J.A. Frederiks (1849-1931) was appointed as supervisor of the work.The restoration took place on the basis of an archeological and building-historical research that was as reliable as possible. The work was accurately documented by means of drawings, photographs and a written report. The architect tried to reuse still existing material for the work.Frederiks probably aimed at restoring the complex to what he considered its 'original state', by which he probably referred to the second half of the sixteenth century, when the complex first obtained the function of Court of the province of Zeeland.In certain situations Frederiks took decisions on an 'aesthetic basis', so that he could create a square that possessed the historical atmosphere expected of it. This restoration was approved by the architect P.J.H. Cuypers. In the light of later, early twentieth-century ideas on restoration, the restored complex was regarded as a 'style imitation'.Due to the German bombing on 17 May 1940 and the subsequent second restoration, the first restoration has more or less passed into oblivion.  The complex owes its present appearance to a second, post-war restoration by the government architect Henri (Hans) de Lussanet de la Sablonière (1907-2002).The policy of the rebuilding of the Abbey complex in Middelburg was under the direction of the Government Buildings Agency, under the supervision of the government commission for the Preservation of Monuments and Historic Buildings. The project dragged on for more than thirty years, balancing between numerous financial, bureaucratic and practical problems.The restoration plan drawn up by De Lussanet, was accurately illustrated by himself in various reports. Part of the complex, which had been totally destroyed, was replaced by new construction after a design of ir. J.F. Berghoef (1903-1994).The ideological backgrounds of the restoration architects, Frederiks and De Lussanet de la Sablonière was quite different. De Lussanet was given the opportunity to restore the Abbey complex to the original state of before the first restoration, but opted for a compromise between the ideas on restoration of his own time and respect for the previously executed restoration. The result of his choice is an elegant and monumental, impressive complex.